Impact of autoimmune thyroiditis on primary hyperparathyroidism (Journal of Medical Science, 2023)
Aim. Primary hyperparathyroidism (PHPT) often coexists with thyroid diseases. Current guidelines advise preoperative ultrasound (US) examination of the thyroid gland for thyroid nodular disease or concomitant malignancy but not evaluation for autoimmune thyroiditis (AIT). The impact of autoimmune thyroiditis on the clinical presentation and intraoperative course of PHPT is not clear. Material and methods. We retrospectively assessed the medical records of 21 patients with PHPT who underwent parathyroidectomy. Clinical, biochemical, ultrasonographic and intraoperative data were evaluated. Results. There was a longer duration of parathyroidectomy in patients with AIT than in those without (113.3 min vs. 93.9 min, P=0.03). A lower rate of kidney stones was noted in patients with autoimmune thyroiditis (44.4% vs. 0%, P=0.03). Patients with AIT were more symptomatic, but this was not significant. There was no difference between the two groups in the prevalence of osteoporosis or thyroid nodular disease. Conclusions. A significantly longer duration of parathyroidectomy was seen in PHPT patients with AIT. Patients with PHPT undergoing surgery should be investigated for autoimmune thyroiditis, as this may affect surgical planning.